Optimalisasi Pencegahan Stunting melalui Edukasi Pengolahan Menu Variatif dan Porsi Makanan Ekonomis Makanan Balita terhadap Upaya Pencegahan Stunting - Marhamah Marhamah; Riski Novera Yenita; Wira Ekdeni Aifa; Hirza Rahmita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of education on varied menu preparation and economical portion sizes for toddlers on stunting prevention efforts in the Lubuk Kandis Community Health Center (Puskesmas) working area in Indragiri Hulu Regency. The research method used a quantitative approach with a pre-experimental design using a one-group pretest-posttest. The results showed a Z-value of -5.657 with a p-value of 0.000 (<0.05), indicating a significant effect of education on improving mothers' understanding of varied menu preparation and economical portion sizes for toddlers. This education helped mothers understand how to prepare nutritious, affordable meals that meet their child's growth and development needs. The conclusion, education on varied menu preparation and economical portion sizes has proven effective in improving stunting prevention efforts. Therefore, similar educational activities need to be implemented on a scheduled, ongoing basis to ensure consistent improvement in mothers' knowledge. Keywords: Toddlers, Nutrition Education, Economical Portion Size, Varied Menu, Stunting Prevention, Stunting